Clinical Spectrum and Early Renal Functional Variability in a Nationwide Greek Pediatric HNF1B Multicenter Cohort - John Dotis; Argyroula Zampetoglou; Varvara Askiti; Maria Bitsori; Ekaterini Siomou; Chrysoula Kosmeri; Nikoleta Printza; Antonia Kondou; Athina Ververi; Charalampos Kapogiannis; Anastasios Kapogiannis; Despoina Tramma; et al. (Journal of Clinical Medicine, 2026)
Background/Objectives: Hepatocyte nuclear factor 1 beta (HNF1B)-associated disease is a major monogenic cause of pediatric cystic kidney disease. This study characterized the clinical, genetic, renal, and extrarenal spectrum of HNF1B-associated disease in a nationwide Greek pediatric cohort, with emphasis on renal functional variability during childhood. Methods: In this retrospective multicenter cohort study, 20 children aged